Implications of racial/ethnic classification in the Hungarian post-genomic medical discourse - Szamosi, Barna (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2022)
Racial/ethnic categorization in medicine presents challenges for clinicians and patients alike. Challenges arise because racial/ethnic identities do not match with objective biolo- gical traits, and at the same time, these identities do have medical consequences in a racially and ethnically stratified society. Three major epistemological approaches – biological realism, eliminativism, and constructivism – dominate scientific theorization on the con- sequences of racial/ethnic categorization in medicine. In this paper, I present a case study of Hungarian medical genetic discourse that focuses on the possible applications of race/ ethnicity regarding Roma and non-Roma patients. In applying the methods of constructivist grounded theory, I recorded and analysed 34 expert interviews with human geneticists between 2011 and 2015. In this paper, I argue that the constructivist understanding of medical diagnoses must be complemented with materialist sensitivity, thus making sense of the contingent nature of race/ethnicity as factors that contribute to medical understanding.
Keywords: enakost na področju zdravja; medicinska genetika; rasna in etnična pripadnost; Romi